1966
DOI: 10.1161/01.res.19.3.552
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Nucleic Acid and Protein Levels with Myocardial Growth and Hypertrophy

Abstract: The myocardial DNA, RNA, actomyosin, and total protein concentrations were determined in rat ventricles ranging between 251 and 1635 mg. Three phases of myocardial growth were evident. Phase 1 (ventricular weights less than 550 mg): DNA concentrations remained relatively constant with increasing ventricular weight. The increasing total DNA per ventricle suggests continuing mitotic activity. Phase 2 (ventricular weights between 550 and 1000 mg): total DNA per ventricle remained relatively constant; with ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

1968
1968
1989
1989

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…XXVII, It has been demonstrated that rapid muscle growth is associated with an increase in the intracellular concentrations of free amino acids (13,14) as well as increased UNA synthesis and content, and increased rates of protein synthesis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Whether the increased intracellular concentration of amino acids determines the increased rate of protein synthesis or is merely a consequence of enhanced substrate requirements is presently unclear (13,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XXVII, It has been demonstrated that rapid muscle growth is associated with an increase in the intracellular concentrations of free amino acids (13,14) as well as increased UNA synthesis and content, and increased rates of protein synthesis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Whether the increased intracellular concentration of amino acids determines the increased rate of protein synthesis or is merely a consequence of enhanced substrate requirements is presently unclear (13,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the biochemical characteristics of the hypertrophied heart have been described in the intact heart following banding of the aorta and pulmonary artery, or in an overloaded perfused heart Received February 25, 1970; accepted for publication July 7, 1970. preparation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). While the loading of the myocardium is altered by these techniques, their complexity does not permit a definition of the specific mechanical stimuli which induce hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators induced cardiomegaly in adult animals by aortic banding or by producing aortic insufficiency and observed in the enlarged hearts an increase in total DNA but a slight decrease in its concentration (1)(2)(3). These findings would indicate both hypertrophy and hyperplasia of cardiac cells.…”
mentioning
confidence: 99%
“…In line with these facts, deoxyribonucleic acid (DNA) of the heart muscle should be newly synthesized and increased, since it has been generally accepted that the DNA content per nucleus is constant in diploid somatic nondividing nuclei within the same species.2-4 Although numerous studies have been made on nucleic acids, there are only a few reports on DNA content of the heart muscle, especially in relation to myocardial growth or cell division. 5,6 It is the purpose of this paper to present evidence supporting our view of cell division of the heart muscle from the determination of DNA content in the whole heart muscle and of DNA content per each heart muscle cell as well as each interstitial cell.…”
mentioning
confidence: 82%